ANALISIS KEBIJAKAN PENANGANAN PENGANGGURAN TERDIDIK DI INDONESIA - Atik Septi Wurvaningsih (LP3 UMY, 2015)
In the first slage of its long-lerm developmenl, Indonesia had heen able to develop ils econonry so thal il moved front poor country slalus lo a middle-income counIry. However, lhe success in lhe ecanomy had nol been followed in the labor sector. Huge number oftmemployment is an indicator of that failure. According to SUPAS 1995 data, the rate of open unemployment of highly educaled workforce reached l2.4 percent from the total workforce. Although it seems that the number is not big, it is indeed a sigVifcant numbel for laborforce with high education backgyound.